Assessment of Barley Genotypes Response to Salinity Stress at Early Seedling Growth Stage: Salinity Tolerance and Stability in Barley (Biological Sciences - PJSIR, 2020)
This study was performed to assess several indices for identifying barley genotypes at early growth stage with the best performance in salinity conditions. The effect of salinity treatments was studied through an analysis of the dry matter production, results showed significant differences among genotypes. The majority of used tolerance indices indicated that ESBYTM8910, 4 Shori and MBS8715 were the best barley genotypes showing the highest stress resistance for the greatest NaCl concentration. It is based on used stability parameters that the genotypes MBS8712 and Jo torsh were the most phenotypically stable. In general, the tolerant genotypes showed the least stability based on mostly of stability parameters